2013
DOI: 10.1093/poq/nft006
|View full text |Cite
|
Sign up to set email alerts
|

An Interactional Model of the Call for Survey Participation: Actions and Reactions in the Survey Recruitment Call

Abstract: Previous research has proposed that the actions of sample members may provide encouraging, discouraging, or ambiguous interactional environments for interviewers soliciting participation in surveys. In our interactional model of the recruitment call that brings together the actions of interviewers and sample members, we examine features of actions that may contribute to an encouraging or discouraging environment in the opening moments of the call. Using audio recordings from the 2004 wave of the Wisconsin Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Thus, the present paper is based on 105 survey calls. In providing direction for interaction coding of the larger, probability sample from the entire WLS study, the practices identified by way of this initial sequential analysis, which draws in part on a master's thesis (Hollander, 2009) by the second author, informed a more comprehensive CA examination of requesting participation (Maynard et al, 2010) as well as the quantitative study (Schaeffer et al, 2013) examining the effects of interviewer practices on odds of gaining respondent participation. 3 …”
Section: Background Data and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the present paper is based on 105 survey calls. In providing direction for interaction coding of the larger, probability sample from the entire WLS study, the practices identified by way of this initial sequential analysis, which draws in part on a master's thesis (Hollander, 2009) by the second author, informed a more comprehensive CA examination of requesting participation (Maynard et al, 2010) as well as the quantitative study (Schaeffer et al, 2013) examining the effects of interviewer practices on odds of gaining respondent participation. 3 …”
Section: Background Data and Methodologymentioning
confidence: 99%
“…If we only had anecdotal evidence like these illustrations, such an assertion would be on shaky grounds, but a recent paper from this project (Schaeffer et al, 2013), using the larger 506-member WLS subsample, addresses the issue along with other complexities to the opening of survey calls by examining the entire introduction quantitatively using multiple regression techniques. That study sheds light on the specific phenomenon of asking for another, while also probing the relevance of related features in the introduction, including reference to and description of the advance letter sent to the household, two types of emergent respondent questions (about the length and content of the interview), laughter tokens and others.…”
Section: Asking For Another: How Formality and Informality Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature shows that interviewers vary in rapport behaviors, such that increased verbal communication, friendliness, and projecting a positive self-image are related to response rates (e.g., Jäckle et al 2013;Schaeffer et al 2013), although, the relationship between the personality trait of agreeableness and cooperation are less conclusive (e.g., Dutwin et al 2014). Rapport behaviors occur during question administration but are inconsistently linked to data quality (Schaeffer et al 2010).…”
Section: Rapport Rapportmentioning
confidence: 99%